Application of Kirinyuh Extracts (Chromolaena odorata (L.) R.M. King and H.E. Rob.) to Germination and Growth of Jawan Grass Weed (Echinochloa cruss-galli) - nurul kholifah (Mulawarman University, 2018)
The objectives of this research were to know: 1) the effect of allelopathy from leaf and kirinyuh root extracts (Chromolaena odorata L.) to suppress seed germination of jawan grass weed (Echinochloa cruss-galli); 2) the influence of allelopathy from leaf and kirinyuh root extracts (C. odorata L.) to suppress the growth of jawan grass weed (E. cruss-galli). This research was conducted from August to October 2017. Sampling site was located in Bukit Raya Village, Samboja District.This study used a Completely Randomized Design consisted of two factors with five treatments and three replications. The first factor was the source of the extracts, consisted of leaves and roots of kirinyuh, while the second factor was the concentration of extracts, namely 0; 50; 100; 150; and 200 gL-1 aquadest. Data were analyzed by analysis of variance with F-test and followed by LSD test of 5% level.The results showed that: 1) kirinyuh extractswas able to inhibit the time and percentage of seed germination of jawan grass weed. The longest in germination time, was 8.54%,obtained from kirinyuh root extracts 200gL-1aquadest. , while the lowest in germination percentage obtained from 50g kirinyuh root extractsL-1, was 40.28%; 2) Leaf and kirinyuh root extractsinhibit thegrowth (height and root length), and caused high percentage of deaths of jawan grass weed. The highest percentage of weed deaths due to kirinyuh leaf extracts of concentration 100 g L- l with the death percentage was 1.76%.